Pengaruh Strategi Belajar Concept Mapping terhadap Hasil Belajar Siswa pada Materi Garis dan Sudut di Kelas VII MTs Negeri 2 Langkat - Rais, Muhammad Rijali; Nisa, Chairun (Indo-MathEdu Intellectuals Journal, 2025)
The learning outcomes of the students showed unsatisfactory results with the average score obtained from 35 students being 53,68 which was very far below the KKM that had been set. This is due to the process of choosing inappropriate learning strategies so that students are not motivated to take lessons. The research aims to determine the effect of Concept Mapping learning strategies on student learning outcomes on lines and angles material in Class VII. The research method used is the experimental method. The design of this study is the One Group Pretest Posttest Group Design. The population in this study were all students of class VII consisting of 5 classes totaling 200 students. The research sample, namely class VII-2, was selected using a simple random sampling technique. Research data was collected using a test consisting of 10 questions. The data analysis technique uses a two-party test as seen from the Paired Sample T-Test in the SPSS Version 18 For Windows program. The research results show that there is a significant influence of concept mapping learning strategies on student learning outcomes. This is because the value of Sig. (2 Tailed) is 0.000 < 0.05 obtained from the output of the Paired Sample T-Test.